A Theoretical Discourse of Substance Abuse and Security Threat among Nigerian Youths; Current Literatures and Interrogations - Ogunmefun Folorunsho Muyideen; Aborisade Richard Abayomi; Aluko Tolulope Evelyn (RIRAI Publisher, 2022)
The ever increasing menace associated with substance or illegal drug consumption among the Nigerian youth is endemic and it has posed as serious challenges and threats toward achieving progressive growth and development on the part of the families, community members, medical practitioners, social workers and other researched area throughout the world. Several publications articulated claim that youths are the future leaders of tomorrow due to their unique characteristics. Unfortunately when denied access to showcase their talents, the situation result to antisocial behaviour (trauma, dependency, larceny,/thefts, poor manpower development among others) that may hampered human and societal development Strain theory, Rational Choice theory and Structural Functionalism were adopted. Content analysis method was adopted in reviewing various publications from Jstor, Scopus, PDF, and Scholarly Google among others. The consequence of increase in security issues can be related to several factors which include illicit drug usage, poor parenting style, peer pressure, poor role modelling. On these grounds, the following recommendations were make- the parent should by all means socialized their children in the way of the Lord so that they will not depart from it, de-associate themselves from negative or bad company as friends or role model, the government at all levels should create recreation, sports centres for the youths to channel their youthful energy, more of public awareness should be carried out in various communities to awake the moral consciousness of the youths concerning negative consequences associated with illicit drug intake